Research on Hybrid Voltage-Power Switching Control Strategy of Grid-Connected Two-Stage Photovoltaic System for Low Voltage Ride Through Faults - Yangyang Wu; Tianshu Wen; Huayu Yuan; Caiqiang Zhang; Xiaolong Song; Peng Bai; Hengshan Xu; Dikang Wang; Kanghui Li; Xianjin Zeng; Siwei Wang (IEEE Access)
For two-stage grid-connected photovoltaic (PV) system, if the low voltage ride through (LVRT) faults occur in the grid side, because the grid voltage falls to a relative low value and the output current is limited, then the output power of inverter reduces and the dc bus voltage fluctuates, which leads the instantaneous dc bus voltage higher than the normal voltage and brings overvoltage breakdown risk. To solve the above problem, in this paper, a hybrid voltage-power switching control strategy for two-stage grid-connectedPV systemis proposed. If the grid voltage is normal, the dc-dcstage works in maximum power point tracking (MPPT) mode, and the inverter works in double-loop control (DLC)mode. If the LVRT fault occurs in grid side, the dc-dc stage switches from MPPT mode to voltage control mode, and the inverter switches from DLC mode to single-voltage-loop control (SVL) mode, that is to say, the two stages switch to voltage control mode to stabilize the dc bus voltage. To verify the effectiveness of the proposed hybrid voltage-power switching control strategy, an experiment is conducted based on the RT-LAB real-time platform (OPAL-RT 5707XG simulator with 8 CPU cores and OPAL-RT Linux OS). The experimental results show that the proposed hybrid control strategy can decrease the voltage ripple ratios by about 0.7%, 16.9%, and 70.3% for 80%, 20%, and 5% LVRT faults, respectively.